(untitled) (World Bulletin of Social Sciences, 2023)
In this article, the implementation of the priority directions of the state policy in the field of higher education in our country, including the Surkhandarya region, reforms in the field of education, their stages and development. Processes related to the implementation of laws and decisions adopted in the field of higher education in our country. , President Sh.Mirziyoyev showed about the establishment of the third renaissance in our country, its creation. Currently, another important process of renaissance is taking place in our country. Therefore, the words "New Uzbekistan" and "Third renaissance" sound harmoniously and harmoniously in our lives, encouraging our people towards great goals. in connection with this, a number of achievements were made in the higher education system of Surkhandarya region. Positive changes are being implemented, such as granting financial independence to higher education institutions and transition to digitization.